Variaciones geográficas de Pyrrhura frontalis (Aves, Psittacidae) - Darrieu, Carlos A. (1983)
Geopaphic variation in the Reddiah-bellied Parakeet (Pyrrhura frontelis ). Geographic variation in the widespread (NE Argentina to NE Brazil). Reddish-bellied Parakeet is not well understood, particularly the distribution of subspecies chripepe and the validity of the race Kriegii and its presence in Misiones. We studied 208 specimens collected at 63 localities, and we recognize only two subspecies P. frontalis (reddish tail) and P. chiripepe (green-yellow tail). We think convenient to include in the rust subspecies all the red-tailed populations; thus we do not recognize the alleged race kriegii. The variation in tail color is clinal, and it is impossible to segregate intermediate specimens in another race. The raee frontalis is distributed from Babia to Sao Paulo in Brazil, and the race chiripepe is distributed from south Rio de Janeiro, Sao Paulo and south Matto Grosso to Rio Grande do Sul (Brazil) and to Chaco and Corrientes in Argentina, as well as SE Paraguay.